ANALISIS QUALITY OF SERVICE (QOS) PADA JARINGAN INTERNET DI UNIVERSITAS BINA INSAN LUBUKLINGGAU MENGGUNAKAN METODE HIERARCHICAL TOKEN BUCKET (HTB) - Armanto, Armanto; Daulay, Nelly Khairani (Jurnal Digital: Telnologi Informasi, 2020)
Abstract - One problem that is often faced by internet users is slow internet access. Specifically, when there are many users sharing internet bandwidth. This problem can occur because no bandwidth management system is used. Therefore it is necessary to apply the appropriate bandwidth management, one of which is HTB. Bandwidth management with queuing bandwidth lending techniques between classes or users. Which can allocate bandwidth according to user bandwidth requirements according to specified priorities. This study uses data collection methods, by observing and recording directly at the research site (observation), conducting question and answer directly to the source (Interview), and documentation by reading literary books. The results obtained from the measurement of QoS parameters using the HTB method on the Bina Insan University network, it can produce an average QoS index value of 3, and included in the category is good. It can be concluded that the HTB method is feasible to be applied at UNIBI in performing bandwidth management as evidenced by the 3 (three) QoS index value and has a  good category.  Keywords: Quality Of Service, Hierarchical Token Bucket, Computer Network